Sanctuary Says. Issue 1 (1st June 2021) - Délano Alonso, Alexandra; Farman, Abou; McNevin, Anne; Ticktin, Miriam
Abstract: In 2018, the New School Working Group on Expanded Sanctuary collaboratively organized a series of workshops in New York to reflect on the question of sanctuary as a conceptual and practical starting point for cross-coalitional politics, including its tensions and risks. This short piece is an attempt to bring together the sentiments expressed in those workshops by activists, organizers, students and academics focusing on anti-racist, pro-migrant, and pro-Indigenous struggles, in a form that engages sanctuary as an ongoing question.